Mahatma Gandhi se Modi - Acharya, Rajeshkumar (Ahmedabad Nanoland, 2016)
One of the unique aspects of Mahatma Gandhi is that he had not left any subject untouched in his speeches and writings. His thoughts and ideology, for examples about education, health, rural development, employment, female development, and industrial development have relevance today even. His mind was versatile and of wide range of interest. His Charkha and Khadi had provided livelihood to millions. Charkha enabled seven hundred thousand villages to become self-contained. His Swadeshi doctrine was founded on the basic principle of using indigenous things and thereby provides livelihood and employment to the countrymen. He believed that much of the deep poverty of the masses is due to the ruinous departure from Swadeshi in the economic and political life. He named the poor as Daridra narayan (God of the Poor). He wanted Swaraj for those toiling and unemployed millions. He wanted a woman to entitle a supreme place in her own sphere of activity as man is in his. His persistence for cleanliness was beyond imagination. He taught the countrymen that cleanliness is Godliness. These issues have been discussed in the relevant chapters. Narendra Modi has always admirer of Mahatma Gandhi. He often quotes Gandhiji in his speeches. His development model rooted in Gadhian ideology. He launched the Swachh Bharat, or Clean India, Mission on October 2, 2014, the birth anniversary of Mahatma Gandhi. He launched Pradhan Mantri Jan Dhan Yojna (PMJDY) for financial inclusion of the mass. He launched Make in India campaign to invite foreign manufactures to manufacture in India on line of Swadeshi doctrine of Mahatma Gandhi. He launched the Pradhan Mantri MUDRA (Micro Units Development and Refinance Agency) Yojana to support the small entrepreneurs.
Keywords: Politics and government